2017
DOI: 10.1080/00365521.2017.1397736
|View full text |Cite
|
Sign up to set email alerts
|

Persistent symptoms in patients with Crohn’s disease in remission: An exploratory study on the role of diet

Abstract: Our exploratory study suggests that dietary interventions such as an elimination diet may reduce GI symptoms in patients with CD in remission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…While the success of available exclusion diets is limited, we may be overlooking the potential of an antigen-response based exclusion diet. Patients with IBD have been shown to have significantly higher rates of food hypersensitivity (allergies and intolerances), and encouraging results have been observed in response to IgG or IgE-titre based exclusion diets [ 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 ]. Further research in this area using objective measures of disease activity is needed to determine if the intake of specific dietary antigens correlates directly with IBD symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…While the success of available exclusion diets is limited, we may be overlooking the potential of an antigen-response based exclusion diet. Patients with IBD have been shown to have significantly higher rates of food hypersensitivity (allergies and intolerances), and encouraging results have been observed in response to IgG or IgE-titre based exclusion diets [ 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 ]. Further research in this area using objective measures of disease activity is needed to determine if the intake of specific dietary antigens correlates directly with IBD symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…However, a 2009 Cochrane review found “uncertain” effects of elimination and vegan diets as a result of inadequate data reporting (92); little if any research has since been published on the effects of elimination diets on RA. The lack of recent research on this topic is concerning, since emerging research has shown that diets eliminating specific foods can be effective for other inflammatory and autoimmune conditions, such as Crohn's disease (93, 94) and eosinophilic esophagitis (9598). Eliminating gluten has also been found to not only ameliorate intestinal signs and symptoms in celiac disease (CD) but also to improve arthritis/arthralgia in some CD patients (99, 100).…”
Section: Associations Between Diet and Ramentioning
confidence: 99%
“…One-third of IBD patients underwent IBS-like symptoms, and partial exclusion of some fermentable components may be associated with benefits to functional symptoms. For example, in a small study with 16 CD patients in remission, a strict exclusion diet of wheat and dairy products for 2 weeks significantly decreased function symptoms such as abdominal pain [68]. In a prospective study with 89 IBD patients in remission, a low-FODMAP diet for 6 weeks reduced IBS-like symptoms while it increased quality of life in patients [69].…”
Section: Exclusion Dietsmentioning
confidence: 99%